THE RELATION OF SELF-PRESENTATION AND COMPULSIVE BUYING - Nur Pratiwi; Narto Irawan Otoluwa (Hasanuddin Journal of Applied Business and Entrepreneurship, 2018)
Over the year the marketing world has turn into a massive change, it is mostly caused by more consumers did the buying activity merely not due to their needs of the products but instead of their wants, while some others did buy as an escape of stress or anxiety feeling, not to mention the existence of more stores, more products, more influencer has major impact to the buying behavior of a customer. This research aims to investigate the relation of this so called self-presentation and compulsive buying, as mention earlier customers buying activity has change, it was no longer needs instead it became habit that can lead to abruption or addicted behavior. One of many addicted behavior is compulsive buying. This research applied multiple regression as an analytical tool as an attempt to measure the relation between self-presentation and compulsive buying. Self-presentation is a way of people to present their self to others, some people present their true self while some use a perfect persona, self-presentation proved has a relation with compulsive buying, but only one dimension out of two proved has significant effect toward compulsive buying. Self presentation has two dimension which are protective style and acquisitive style, the protective style proved has no significant effect toward compulsive buying while acquisitive style prove has significant effect toward compulsive buying.